المعالم الأثرية بوادي سوف بين الانهيار والترميم - ماني, محمد (جامعة الوادي University of Eloued, 2017)
يزخر وادي سوف كغيره من الوطن الجزائري بموروث حضاري مادي مهم، متمثل في المخطوطات الكامنة في زوايا المكتبات ورفوف الخزائن العتيقة، و من هذا الموروث المادي توجد المعالم التاريخية، التي كانت تمثل منارات علمية أو إدارية مهمة في هذه المنطقة. إن بلدة قمار تعتبر من البلدات الأول من حيث النشأة على تراب سوف، إن مقر الحكم لهذه البلدة - ديوان القائد - أكبر دليل على الموروث الأثري السوفي الجزائري، إن تاريخ إنشاء هذا المقر قديم جدا لا يعرف بالتحديد ولكن كيف هي الحالية العمرانية لهذا المنشأ؟ وما هي أهم المشاكل الإنشائية التي تعاني منها؟ وهل من سبل لاستغلالها من جديد في إطار يخدم الوجهة الاجتماعية على جميع الأصعدة؟ لقد تميزت منطقة وادي سوف بوجود مواد جبسية مختلفة استغلت من طرف السكان في بناء ما يحتاجونه من عمارة لأغراضهم المختلفة، و قد عانت هذه المواد بعد مرور السنين و الأعوام من الفتور و الإعياء ، فهل من آليات و وسائل محلية تستطيع رد الاعتبار لهذه العمارة ، بطرق حديثة تستغل المواد المحلية الأخرى التي يمكن بها تقوية البناء و العمارة ، مثل اللألياف النباتية الخاصة بالمنطقة ، لهذا وسمت هذه المداخلة بــ " المعالم الأثرية الجبسية بين الانهيار و الترميم " إن مختلف المعاينات و الدراسات التي قمنا بها أثبتت في مجملها أن المنشآت الجبسية معرضة للتشققات و الإعياء شأنها شأن المنشآت الخرسانية و غيرها و أنه بإمكاننا ترميمها بمواد محلية شبيهة بالتي بنيت بها ، و بهذا يمكننا بعثها و استغلالها من جديد . Oued souf, like other regions in the Algerian homeland, is replete with an important cultural heritage, exemplified by the manuscripts that lie in the corners of the libraries and the shelves of the antique safes, historical monuments are located within this heritage, which were used to represent important scientific or administrative beacons in this region. Guemar is one of the towns that was first founded in Souf, and the office of authority -the Commander’s Office/Deewan elkayed- is indeed the greatest evidence of the ancient Soufi heritage, the date of creation of this office is too old to be defined, but how is the current physical state of this structure? What are the most important structural problems that it suffers from? Are there any ways of exploiting them again in a socially oriented framework? Oued souf has been marked by various gypsum materials that, for various purposes, have been used by the population to build what they needed. Over the last years, these substances have suffered from apathy and weariness. The question is: are there Any local mechanisms and means that can rehabilitate this kind of architecture in a modern way by exploiting other local materials that can strengthen the building? For instance, the region's own botanical fibers, for this reason, this intervention is called "gypsy monuments; collapse and restoration." The various previews and studies we have conducted have shown in their entirety that gypsum establishments are prone to cracks and weariness, exactly like concrete structures and others, we can restore them with local materials similar to those they were built in, thus, they can be exploited anew.
Keywords: المعالم الأثرية، الترميم، التشققات، الجبس، ألياف النخيل